1995
DOI: 10.1074/jbc.270.43.25445
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Troponin I Mutants

Abstract: 2؉sensitivity of the myofilament.It is suggested that Ser-43/Ser-45 and Ser-23/Ser-24 in cardiac TnI are important for normal Ca 2؉ sensitivity of the myofilament, and that phosphorylation of Ser-43/ Ser-45 and Ser-23/Ser-24 is primarily involved in the protein kinase C regulation of the activity and Ca 2؉ sensitivity, respectively, of actomyosin S-1 MgATPase.In cardiac myocytes, the activation of several types of receptors, such as ␣ 1 -adrenergic (1-5), muscarinic (1, 6), and purinergic (6) dynorphin A (7), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
173
3
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(197 citation statements)
references
References 77 publications
20
173
3
1
Order By: Relevance
“…3 and 4). Although phosphorylation of cTnI by PKC can occur at Ser 43 / Ser 45 and Thr 144 , which decreases the myofilament Ca 2ϩ sensitivity (18,39,40), our results coincide with previous studies (31), which show that serines 23 and 24 are the only two sites basally phosphorylated in vivo within the WT murine cTnI protein. These findings suggest that one or more of the following may occur in the murine heart: 1) phosphorylation of Ser 23 / Ser 24 is dominant over the phosphorylation of Ser 43 /Ser 45 and Thr 144 and/or 2) PKC-mediated phosphorylation of cTnI does not increase as a compensatory mechanism for the decrease in PKA-mediated phosphorylation.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…3 and 4). Although phosphorylation of cTnI by PKC can occur at Ser 43 / Ser 45 and Thr 144 , which decreases the myofilament Ca 2ϩ sensitivity (18,39,40), our results coincide with previous studies (31), which show that serines 23 and 24 are the only two sites basally phosphorylated in vivo within the WT murine cTnI protein. These findings suggest that one or more of the following may occur in the murine heart: 1) phosphorylation of Ser 23 / Ser 24 is dominant over the phosphorylation of Ser 43 /Ser 45 and Thr 144 and/or 2) PKC-mediated phosphorylation of cTnI does not increase as a compensatory mechanism for the decrease in PKA-mediated phosphorylation.…”
Section: Discussionsupporting
confidence: 81%
“…Deletion of cTnI residues 2-26 in a transgenic mouse model facilitated the diastolic and systolic functions of both young and aged hearts (15,16). Furthermore, it has been shown that phosphorylation within the cTnI N-terminal extension: 1) increases the rate of relaxation and cross-bridge cycling kinetics (17)(18)(19); and 2) decreases both the Ca 2ϩ affinity of cTnC (20) and the Ca 2ϩ sensitivity of force generation (19). Altogether, these reports indicate that a major role for the cTnI N-terminal extension is to assist in the lusitropic effects of cardiac muscle relaxation (14).…”
Section: Hypertrophic Cardiomyopathy (Hcm)mentioning
confidence: 99%
“…Cardiac TnI also can be phosphorylated by PKC at Ser-42 and Ser-44 in the N-domain and Thr-143 in the inhibitory region of cTnI [57]. Phosphorylation at Ser-42/Ser-44 is known to decrease maximal actomyosin Mg 2+ ATPase activity and Ca 2+ -sensitivity by stabilizing the inactive state of the thin filament [24][25][26]58].…”
Section: Molecular Mechanisms Of the Effects Of Ctni Phosphorylation mentioning
confidence: 99%
“…␤-Adrenergic stimulation leads to protein kinase A phosphorylation at Ser 23 and Ser 24 of cTnI, enhancing relaxation by decreasing the Ca 2ϩ affinity at site II (7,8). Cardiac TnI can also be phosphorylated by PKC at Ser 43 , Ser 45 , and Thr 144 (9). Phosphorylation at Ser 43 and Ser 45 is known to decrease maximal actomyosin MgATPase activity, Ca 2ϩ sensitivity, and cross-bridge binding to the thin filament (4, 9 -11).…”
mentioning
confidence: 99%